Thermosiphonic Hybrid PV/T Solar Systems - Souliotis, Manolis; Tripanagnostopoulos, Yiannis; Kalogirou, Soteris A. (My University, 2009)
Thermosiphon solar water heaters and Photovoltaic (PV) devices are well known solar systems that provide heat and electricity, respectively. In this work, these two systems are combined into a hybrid hotovoltaic/Thermal (PV/T) solar system which can simultaneously provide electricity and heat, thus achieving a higher conversion rate of the absorbed solar radiation than standard PV modules. When properly designed, PV/T systems can extract heat from PV modules which can be used to heat water or air. By doing so the operating temperature of PV modules is reduced, which is beneficial, as it keeps their electrical efficiency at a sufficient level. In this paper, the design considerations and experimental results of a thermosiphonic hybrid PV/T solar system are presented. The electrical and thermal energy output for a pc-Si PV/T module type under the climatic conditions of Patras are presented.
Keywords: PV/T collectors; Commercial photovoltaic; ICS solar water heaters